Análisis comparativo del rendimiento térmico entre un colector solar de placa plana y la adhesión de aletas en la placa absorbente. - Remache Sasig., Milton Xavier (2021)
Solar collectors absorb radiation on absorbing plate and convert it into thermal energy that is transfer to the fluid that circulates through collecting chamber, applications are very wide, such as for heating homes or hospitals, drying wood, refrigeration systems, and essential for agricultural studies beginning about drying grains process, among elements that are part of solar collector, there are plate, collection chamber where greenhouse effect or duct occurs, protective plate at this case glass, thermal insulation, some factors that affect efficiency system are inclination angle, increase in total area of collector plate through the adhesion of different geometric shapes in rectangular fins, transfer of heat by forced convection with four different mass flows also other parameters such as hydraulic diameter flow, Nusselt number, Reynolds number, difference at inlet and outlet temperatures, heat flow, at obtained results is observed an average outlet temperature of 34.52 ° C, this represents an efficiency value of 64.76 %, to obtain these results, an analysis of solar thermal energy in collector plate, an energy balance in the system, application of theoretical heat transfer formulas and elaboration of tables with obtained data was carried out.